African socialism-success or failure - Hans Cohn (Intereconomics, 1971)
It has contributed a great deal to the problems of many young and inexperienced African states that they have been thrust into an advanced international economic, social and political system. They are expected to fit into this system, although they are sometimes lacking the level of development to do so.
Keywords: 330; Development Policy